2023
DOI: 10.3892/mmr.2023.12939
|View full text |Cite
|
Sign up to set email alerts
|

STEAP1 regulation and its influence modulating the response of LNCaP prostate cancer cells to bicalutamide, enzalutamide and apalutamide

Abstract: anti-androgen drugs are the standard pharmacological therapies for treatment of non-metastatic prostate cancer (Pca). However, the response of Pca cells may depend on the anti-androgen used and often patients become resistant to treatment. Thus, studying how the anti-androgen drugs affect oncogenes expression and action and the identification of the best strategy for combined therapies are essential to improve the efficacy of treatments. The Six Transmembrane epithelial antigen of the Prostate 1 (STeaP1) is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…However, most patients develop resistance to these drugs due to changes in the expression of oncogenes [ 33 ]. Recently, it was shown that STEAP1 did not alter the response of PCa cells to anti-androgen treatment [ 34 ]. Taking into account that there are no studies evaluating the relationship between STEAP1 and taxane-based chemotherapeutics, this study intended to explore the effect of chemotherapeutic drugs in modulating the expression of STEAP1, as well as to evaluate the role of STEAP1 in influencing the response of PCa cells to chemotherapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…However, most patients develop resistance to these drugs due to changes in the expression of oncogenes [ 33 ]. Recently, it was shown that STEAP1 did not alter the response of PCa cells to anti-androgen treatment [ 34 ]. Taking into account that there are no studies evaluating the relationship between STEAP1 and taxane-based chemotherapeutics, this study intended to explore the effect of chemotherapeutic drugs in modulating the expression of STEAP1, as well as to evaluate the role of STEAP1 in influencing the response of PCa cells to chemotherapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that STEAP1 knockdown alone decreased the cell viability in both cell lines, as well as all taxane-based treatments when administered alone. However, the combination between STEAP1 knockdown and exposure to taxane-based therapy led to an increase in cell viability/proliferation and diminished levels of apoptosis [118]. Altough more studies are required, these data suggest that the combination of taxane-based drugs with STEAP1 knockdown may lead to PCa progression.…”
Section: Steap1mentioning
confidence: 95%
“…Although its function remains unclear, some studies have pointed out that STEAP1 is involved in metal reductase activity, and also in transport of ions such as Na + , Ca 2+ , and K + [117]. STEAP1 is highly expressed in LNCaP cells and also at significant levels in C4-2B cell line [118]. Regarding the effect of STEAP1 knockdown in LNCaP cells, reduced cell viability was observed in comparison to the control group.…”
Section: Steap1mentioning
confidence: 97%
See 2 more Smart Citations